Effect of level of non-enzymatically browned soybean meal in limit-fed, grain sorghum diets for growing heifers - Hunter, R.D.; Drouillard, James S.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Grain sorghum-based diets were fed in a limit-feeding trial involving 72 heifers for 100 days. Heifers were fed one of four diets designed to provide 12.5%, 14.9%, 17.3%, and 19.6% crude protein. Protein levels in the diets were altered by providing up to 20% of the diet as non-enzymatically browned soybean meal (Soypassâ) at the expense of dry-rolled grain sorghum. Performance of heifers (gain and feed efficiency) tended (P=.15) to improve linearly as protein concentration of the diets was increased. The greatest improvements were observed at concentrations up to 17.3%.
Keywords: Beef; Bypass protein; Limit feeding